Left Atrial 4D Blood Flow Dynamics and Hemostasis following Electrical Cardioversion of Atrial Fibrillation - Cibis, Merih; Lindahl, Tomas L.; Ebbers, Tino; Karlsson, Lars O.; Carlhäll, Carl-Johan (Frontiers in Physiology, 2017)
Abstract Background Electrical cardioversion in patients with atrial fibrillation is followed by a transiently impaired atrial mechanical function, termed atrial stunning. During atrial stunning, a retained risk of left atrial thrombus formation exists, which may be attributed to abnormal left atrial blood flow patterns. 4D Flow cardiovascular magnetic resonance (CMR) enables blood flow assessment from the entire three-dimensional atrial volume throughout the cardiac cycle. We sought to investigate left atrial 4D blood flow patterns and hemostasis during left atrial stunning and after left atrial mechanical function was restored. Methods 4D Flow and morphological CMR data as well as blood samples were collected in fourteen patients at two time-points: 2-3 hours (Time-1) and 4 weeks (Time-2) following cardioversion. The volume of blood stasis and duration of blood stasis were calculated. In addition, hemostasis markers were analysed. Results From Time-1 to Time-2: Heart rate decreased (61 ±7 vs. 56 ± 8 bpm, p=0.01); Maximum change in left atrial volume increased (8 ± 4 vs. 22 ± 15 %, p=0.009); The duration of stasis (68 ± 11 vs. 57 ± 8 %, p=0.002) and the volume of stasis (14 ± 9 vs. 9 ± 7 %, p=0.04) decreased; Thrombin-antithrombin complex (TAT) decreased (5.2 ± 3.3 vs. 3.3 ± 2.2 ug/L, p=0.008). A significant correlation was found between TAT and the volume of stasis (r2=0.69, p<0.001) at Time-1 and between TAT and the duration of stasis (r2=0.34, p=0.04) at Time-2. Conclusion In this longitudinal study, left atrial multidimensional blood flow was altered and blood stasis was elevated during left atrial stunning compared to the restored left atrial mechanical function. The coagulability of blood was also elevated during atrial stunning. The association between blood stasis and hypercoagulability proposes that assessment of left atrial 4D flow can add to the pathophysiological understanding of thrombus formation during atrial fibrillation related atrial stunning.